Dinamika Gerakan Islam Berkemajuan di Sulawesi Selatan - Hadisaputra Hadisaputra; Mustari Bosra; Eka Damayanti; Fatimah Azis; Andi Asywid Nur (Society, 2024)
This study outlines the concept of Progressive Islam—a term for Muhammadiyah’s religious perspective—both historically and based on the ideological foundations of the Muhammadiyah Organization. After a conceptual explanation, this study analyzes the struggles of Progressive Islam in South Sulawesi through historical aspects and direct observations as a Muhammadiyah activist. The study reveals that the early generations of Muhammadiyah in South Sulawesi implemented the ethos of Progressive Islam through the development of educational and da’wah enterprises. However, the emergence of cadres who established different organizations, such as Hidayatullah and Wahdah Islamiyah, highlights ideological challenges and weaknesses in consistent cadre formation. Furthermore, conservatism among Muhammadiyah members in South Sulawesi poses obstacles to actualizing Progressive Islamic thought, despite efforts to address this through Muhammadiyah’s Tarjih Ulama Education program. This study offers practical benefits by providing recommendations to strengthen cadre formation and organizational consolidation to ensure Progressive Islam remains relevant in addressing contemporary challenges. These dynamics serve as an important foundation for sustaining the progressiveness of Progressive Islam in South Sulawesi.